2022
DOI: 10.1186/s12917-022-03162-2
|View full text |Cite
|
Sign up to set email alerts
|

Photodermatitis and ocular changes in nine horses after ingestion of wild parsnip (pastinaca sativa)

Abstract: Background Primary photosensitization rarely occurs in horses and can easily be misinterpreted. Descriptions of the disease in horses after ingestion of parsnip are lacking. The aim of this case series was to describe the dermatological and ocular changes due to photosensitization and to raise awareness of parsnip being a possible aetiologic agent. Case presentation Nine horses from three different stables in Berlin and Brandenburg, Germany, presen… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Recent investigations have revealed that heraclenol (7) and oxypeucedanine hydrate (8) elicit a mild stimulatory effect on melanogenesis without affecting cell proliferation, as evidenced by studies examining the effect of furanocoumarins on the skin [103]. Moreover, furanocoumarins have been employed in the treatment of vitiligo and psoriasis [107].…”
Section: Pastinaca Sativa L Seler Family -Apiaceaementioning
confidence: 99%
“…Recent investigations have revealed that heraclenol (7) and oxypeucedanine hydrate (8) elicit a mild stimulatory effect on melanogenesis without affecting cell proliferation, as evidenced by studies examining the effect of furanocoumarins on the skin [103]. Moreover, furanocoumarins have been employed in the treatment of vitiligo and psoriasis [107].…”
Section: Pastinaca Sativa L Seler Family -Apiaceaementioning
confidence: 99%
“…Furthermore, furanocoumarins extracted from parsnips have the ability to dilate peripheral vessels and coronary vessels of the heart, eliminate spasms of the bronchi and smooth muscles of the abdominal cavity, and have a moderate sedative effect. In addition, P. sativa exhibits antioxidant and anticytolytic activities [ 256 ].…”
Section: Introductionmentioning
confidence: 99%